FEATURES CALCULATIONS OF DYNAMIC MODES OF THE ELECTRICAL SYSTEM - Iegorov, Oleksiy; Iegorova, Olga; Glebova, Marina; Forkun, Jana (SWorld-Ger Conference proceedings, 2025)
The purpose of the study is to consider modeling the modes of local objects on a single information model within the framework of an automated system for controlling the modes of electrical systems. A mathematical model of the electrical system is propose